DASH DIET EDUCATION AND WORKSHOP INCREASING HEALTH DIETARY PATTERN IN HIPERTENSIVE PATIENT - A A Ayu Asri Prima Dewi; Dharin Serebrina Arfiputri; Mia Rahardjo; Siti Amira Venitarani; Seroja Harsa SB; Wahyu Primadyani (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2026)
Introduction: Hypertension remains a major public health problem in Indonesia, particularly in urban communities, and is strongly associated with unhealthy dietary patterns. The Dietary Approaches to Stop Hypertension (DASH) diet has been proven effective in lowering blood pressure and improving cardiovascular health, yet community awareness and practical application remain limited. This community service program aimed to improve knowledge related healthy dietary pattern. Methods: The activity was conducted using a participatory approach, consisting of structured nutrition education, interactive discussions, and hands-on workshops on DASH diet implementation. This study used a pre-experimental one-group pre–post design involving 18 participants. Participants included adult community members of Rangkah area. Educational materials focused on principles of the DASH diet, food selection, portion control, and daily meal planning. Knowledge about healthy dietary pattern improvement was evaluated using pre- and post-education questionnaires, while participant engagement and feedback were qualitatively assessed. Mean pre and post test was statistically analysis using paired t-test with significant level of p<0,05. Results: A total of 18 community participants actively attended the program. Post-intervention evaluation demonstrated an increase in participants’ understanding of DASH diet principles and healthy food choices. Statistic result showed increasing of mean test result from 75,0 ± 26,18 at pre test info 84,4 ± 19,47 at post test (12,5% improvement) and was statistically significant (p=0,025). Participants showed high enthusiasm during the workshop sessions and reported improved confidence in applying DASH diet recommendations in daily life. Conclusion: DASH diet education combined with interactive workshops effectively enhanced community knowledge and practical skills in hypertension prevention. Collaboration between academic institutions, medical residency programs, and community organizations plays an important role in strengthening community-based nutrition education and promoting sustainable healthy lifestyle behaviors. KEYWORDS clinical nutrition; community medicine; DASH diet; hypertension nutrition